Urban form as policy variable for climate-sensitive area planning under heterogeneity: a geographically weighted regression approach. Issue 2 (2nd April 2020) - Mehrotra, Surabhi; Bardhan, Ronita; Ramamritham, Krithivasan
ABSTRACT: Although built-up areas exacerbate the urban heat island (UHI) effect, the thermal impact of heterogeneous urban areas remains unknown. In this study geographically weighted regression (GWR) is used to examine the locally variable relationship between land surface temperatures (LSTs) and urban built form (UBF) indices. Sky view factor, built coverage, vegetation, building height, distance to ecosystem services and surface elevation are shown to have a significant geographically varying impact on LST and urban heat stress. These UBF variables can serve as urban design instruments, help predict LST and enable the mitigation of UHI effects in heterogeneous urban areas, while GWR offers a local planning tool for the formulation of climate-responsive, local area level development regulations and policies. Abbreviations: BCR, Built Coverage Ratio; BHt, Building Height; DEM, Digital Elevation Model; DistES, Distance from the ecosystem service provider; FSI, Floor Space Index; GWR, Geographically Weighted Regression; LST, Land Surface Temeperature; NDVI, Normalized difference vegetation index; RAR, Road Area Ratio; OLS, Ordinary Least Squares; SUHI, surface urban heat island; SVF, Sky View Factor; TVR, Total Vertical Ratio; UBF, Urban Built Form